The use of facebook for marketing purposes among smes as a modern marketing method – research results from Poland - Chmielecki, M. (Видавництво Львівської політехніки, 2014)
Over the last couple of years social media have transformed the way in which marketing is carried out. The aim of this article is to present barriers that prevent SMEs to use Facebook for their marketing purposes. This article presents the research results carried out in Lodz Voivodship in Poland. За декілька останніх років соціальні медіа трансформували підхід до використання маркетингу. Метою статті є визначення бар'єрів, які заважають малому та середньому підприємництву використовувати Facebook для їх маркетингових цілей. Подано результати дослідження, проведеного в Лодзькому воєводстві в Польщі.
Використання facebook в маркетингових цілях МСП як сучасний метод маркетингу – результати досліджень з Польщі
Keywords: facebook; makreting; SMEs; social media; Łódź Voivodeship; facebook; маркетинг; МСП; соціальні медіа; Лодзьке воєводство